Microbial Communities in the East and West Fram Strait During Sea Ice Melting Season - Fadeev, Eduard; Salter, Ian; Schourup-Kristensen, Vibe; Nöthig, Eva-Maria; Metfies, Katja; Engel, Anja; Piontek, Judith; Boetius, Antje; Bienhold, Christina (Frontiers in Marine Science, 2018)
Climate models project that the Arctic Ocean may experience ice-free summers already in the second half of this century. This may have severe repercussions on phytoplankton bloom dynamics and the associated cycling of carbon in surface waters. We currently lack baseline knowledge of the seasonal dynamics of Arctic microbial communities, which is needed in order to better estimate the effects of such changes on ecosystem functioning. Here we present a comparative study of polar summer microbial communities in the ice-free (eastern) and ice-covered (western) hydrographic regimes at the LTER HAUSGARTEN in Fram Strait, the main gateway between the Arctic and North Atlantic Oceans. Based on measured and modeled biogeochemical parameters, we tentatively identified two different ecosystem states (i.e., different phytoplankton bloom stages) in the distinct regions. Using Illumina tag-sequencing, we determined the community composition of both free-living and particle-associated bacteria as well as microbial eukaryotes in the photic layer. Despite substantial horizontal mixing by eddies in Fram Strait, pelagic microbial communities showed distinct differences between the two regimes, with a proposed early spring (pre-bloom) community in the ice-covered western regime (with higher representation of SAR11, SAR202, SAR406 and eukaryotic MALVs) and a community indicative of late summer conditions (post-bloom) in the ice-free eastern regime (with higher representation of Flavobacteria, Gammaproteobacteria and eukaryotic heterotrophs). Co-occurrence networks revealed specific taxon-taxon associations between bacterial and eukaryotic taxa in the two regions. Our results suggest that the predicted changes in sea-ice cover and phytoplankton bloom dynamics will have a strong impact on bacterial community dynamics and potentially on biogeochemical cycles in this region.